Laws for Protection of Wildlife in India: Need for Awareness towards Implementation and Effectiveness - Samant Singhar, A. (Indian Forester, 2002)
Various laws have been enacted for protection and conservation of wildlife and to stop illegal trade in wildlife in India. These are wanting in view of growing international trade in medicinal plants and other faunal and floral derivatives. To be more effective , these laws are to be implemented with certainty , minimum time taken for awarding punishment and exemplary weight of punishment. Local peoples participation is essential for proper and effective implementation of wildlife protection laws and conservation of wildlife biodiversity.